2014
DOI: 10.1161/circulationaha.114.011675
|View full text |Cite|
|
Sign up to set email alerts
|

LincRNA-p21 Regulates Neointima Formation, Vascular Smooth Muscle Cell Proliferation, Apoptosis, and Atherosclerosis by Enhancing p53 Activity

Abstract: Background Long non-coding RNAs (lncRNAs) recently have been implicated in many biological processes and diseases. Atherosclerosis is a major risk factor for cardiovascular disease. However, the functional role of lncRNAs in atherosclerosis is largely unknown. Methods and Results We identified lincRNA-p21 as a key regulator of cell proliferation and apoptosis during atherosclerosis. The expression of lincRNA-p21 was dramatically down-regulated in atherosclerotic plaques of ApoE−/− mice, an animal model for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
353
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(372 citation statements)
references
References 55 publications
10
353
0
4
Order By: Relevance
“…Huarte et al found that lincRNA-p21, which was a p53-induced lncRNA and function as a component of the p53 pathway, could downregulate various p53 target genes by interacting with p53 repressive complex 59) . Wu et al 60) confirmed that lincRNA-p21 suppresses cell proliferation and induces apoptosis and more importantly, lincRNA-p21 knockdown results in obvious neointimal hyperplasia. They found that lincRNA-p21 enhances p53 activity by directly binding to mouse double minute 2 (MDM2), thus decreasing MDM2-mediated inhibition of p53 and facilitating p53 binding to p300 for acetylation.…”
Section: Long Noncoding Rnas In Smcsmentioning
confidence: 97%
“…Huarte et al found that lincRNA-p21, which was a p53-induced lncRNA and function as a component of the p53 pathway, could downregulate various p53 target genes by interacting with p53 repressive complex 59) . Wu et al 60) confirmed that lincRNA-p21 suppresses cell proliferation and induces apoptosis and more importantly, lincRNA-p21 knockdown results in obvious neointimal hyperplasia. They found that lincRNA-p21 enhances p53 activity by directly binding to mouse double minute 2 (MDM2), thus decreasing MDM2-mediated inhibition of p53 and facilitating p53 binding to p300 for acetylation.…”
Section: Long Noncoding Rnas In Smcsmentioning
confidence: 97%
“…10 Smooth muscle-expressed lncRNAs regulate vascular smooth muscle cell (VSMC) proliferation, migration, and phenotypic switching. 11,12 Hypertension is usually characterized by abnormal vascular tone, which is regulated by vascular smooth muscle-mediated vessel contraction and endothelium-dependent vessel vasodilation. 13,14 We speculated that lncRNAs might regulate vascular tone via affecting endothelial cell (EC) and VSMC function.…”
mentioning
confidence: 99%
“…In another study, it has been demonstrated that lincRNA-p21 suppresses cell proliferation, induces apoptosis, and leads to neointimal hyperplasia along with the knockdown of lincRNA-p21. LincRNA-p21 increases the p53 activity by directly binding to mouse double minute 2 (MDM2); therefore, MDM2-mediated inhibition of p53 decreases and the binding of p53 to p300 is facilitated (40). In another study investigating the role of lncRNAs in smooth muscle cells, angiotensin II has been shown to induce VSMC hyperproliferation and hypertrophy (41).…”
Section: Importance Of Lncrnas In the Cells Involved In The Formationmentioning
confidence: 99%